IMPROVING THE OFFICIAL PROCEDURE OF INTELLIGENCE CONTROL BODIES DURING OPERATION INTELLIGENCE PLANNING - Andrii Saveliev (Sučasnì Informacìjnì Tehnologìï u Sferì Bezpeki ta Oboroni)
The article contains recommendations for improving the official procedure of Intelligence tactical formations based on prioritization of intelligence, reconnaissance and combat missions during the planning of investigation in order to complete the operational and tactical tasks of defensive operations. These recommendations are included into the offered order procedures, techniques and methods for prioritizing intelligence, reconnaissance and combat missions in accordance with the operational and tactical tasks for defensive tactical operations performed by the grouping of troops. Improved order in the defence intelligence operations planning performed by  Intelligence officials in tactical formations enables to consider a further priority of intelligence, reconnaissance and combat missions in the distribution of intelligence on enemy objects, which in turn enhances the performance of such tasks. The Improved order in defence intelligence operations planning performed by Intelligence officials in tactical formations could be recommended to Intelligence agencies for using in defence intelligence planning operations performed by the grouping of troops.